Geometrical Confinement Effects in Layered Mesoscopic Vortex Matter - Cejas Bolecek, Néstor René (2014)
We study the geometrical confinement effect in Bi22Sr22CaCu22O8+δ8+δ mesoscopic vortex matter with edge-to-surface ratio of 7–12 %. Samples have in-plane square and circular edges, 30 μm widths, and ∼2 μm thickness. Direct vortex imaging reveals the compact planes of the structure align with the sample edge by introducing topological defects. The defect density is larger for circular than for square edges. Molecular dynamics simulations suggest that this density is not an out-of-equilibrium property but rather determined by the geometrical confinement.